Tracheostomy in the coronavirus disease 2019 patient: evaluating feasibility, challenges and early outcomes of the 14-day guidance. Issue 8 (6th August 2020) - Glibbery, N; Karamali, K; Walker, C; Fitzgerald O'Connor, I; Fish, B; Irune, E
Abstract: Objectives: To report feasibility, early outcomes and challenges of implementing a 14-day threshold for undertaking surgical tracheostomy in the critically ill coronavirus disease 2019 patient. Methods: Twenty-eight coronavirus disease 2019 patients underwent tracheostomy. Demographics, risk factors, ventilatory assistance, organ support and logistics were assessed. Results: The mean time from intubation to tracheostomy formation was 17.0 days (standard deviation = 4.4, range 8–26 days). Mean time to decannulation was 15.8 days (standard deviation = 9.4) and mean time to intensive care unit stepdown to a ward was 19.2 days (standard deviation = 6.8). The time from intubation to tracheostomy was strongly positively correlated with: duration of mechanical ventilation (r(23) = 0.66; p < 0.001), time from intubation to decannulation (r(23) = 0.66; p < 0.001) and time from intubation to intensive care unit discharge (r(23) = 0.71; p < 0.001). Conclusion: Performing a tracheostomy in coronavirus disease 2019 positive patients at 8–14 days following intubation is compatible with favourable outcomes. Multidisciplinary team input is crucial to patient selection.